2018
DOI: 10.2147/jpr.s175169
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of preemptive analgesia on acute postoperative pain in children undergoing major orthopedic surgery of the lower extremities

Abstract: BackgroundChildren undergoing major orthopedic surgery of the lower extremities can experience severe postoperative pain; yet, the ideal postoperative pain management strategy is unknown. Thus, in this patient population, we investigated the effect of intraoperative epidural infusion of local anesthetic on acute postoperative pain and analgesic consumption.Patients and methodsPatients (N=50, 3–12 years) randomly received either ropivacaine 0.15% (preemptive group) or normal saline (control group) as an initial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Complex spine surgery can be defined as thoracolumbar spine surgery with instrumentation, laminectomy at three or more levels, or scoliosis surgery to improve longterm pain and quality of life in symptomatic patients with back diseases associated with significant postoperative pain (12). Inadequate treatment of postoperative pain can lead to patient dissatisfaction with the surgical experience and may have adverse psychological consequences; so, an essential part of perioperative care is postoperative pain management (13) . Recently, both preemptive analgesia and multimodal analgesia have been proposed with acceptance in addressing pain management (14) In agreement with our results for preoperative anxiety and postoperative satisfaction scores, Vasigh et al (2016) (6) ( who used the same combination of preemptive gabapentin plus celecoxib in the same doses as us) found that the mean anxiety score in the gabapentin group was significantly lower compared to the placebo and gabapentin plus celecoxib group respectively (p < 0.001, p<0.05) without significant difference between gabapentin group and gabapentin plus celecoxib group and also found patient satisfaction was significantly higher in gabapentin plus celecoxib group compared to the placebo and gabapentin group (p< 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Complex spine surgery can be defined as thoracolumbar spine surgery with instrumentation, laminectomy at three or more levels, or scoliosis surgery to improve longterm pain and quality of life in symptomatic patients with back diseases associated with significant postoperative pain (12). Inadequate treatment of postoperative pain can lead to patient dissatisfaction with the surgical experience and may have adverse psychological consequences; so, an essential part of perioperative care is postoperative pain management (13) . Recently, both preemptive analgesia and multimodal analgesia have been proposed with acceptance in addressing pain management (14) In agreement with our results for preoperative anxiety and postoperative satisfaction scores, Vasigh et al (2016) (6) ( who used the same combination of preemptive gabapentin plus celecoxib in the same doses as us) found that the mean anxiety score in the gabapentin group was significantly lower compared to the placebo and gabapentin plus celecoxib group respectively (p < 0.001, p<0.05) without significant difference between gabapentin group and gabapentin plus celecoxib group and also found patient satisfaction was significantly higher in gabapentin plus celecoxib group compared to the placebo and gabapentin group (p< 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…24 Pre-emptive administration of these agents is no longer recommended. 25 Opioid use combined with poorly controlled pain scores postoperatively have been identi ed as risk factors associated with opioid misuse during the postoperative period. 26 Due to current public health concerns regarding addiction to prescription opioids administered postoperatively, that there is a real need to direct our focus towards non-opioid based multimodal analgesic strategies such as fascial plane blocks.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, children with a VAS score greater than 3 points were treated with 0.15-0.20% ropivacaine (initial dose, 6-10 ml; maintenance dose, 4-6 ml/h; aggressive dose: is 2-4 ml; the lockout time, 20-30 min; and the maximum dose, 12 ml/h). In this study, the analgesic dose was selected in reference to the study of Kim et al (26) who applied this dose in the investigation of children with lower extremity orthopaedic surgery, which significantly reduced the pain of children and has extremely high application value. The VAS score at T 2 was 2.93±0.66 in the observation group and 5.37±0.63 in the control group.…”
Section: Discussionmentioning
confidence: 99%